Nursing interventions to reduce surgical site infection in potentially contaminated surgeries: an integrative review - Martins, Tatiana; Amante, Lúcia Nazareth; Vicente, Camila; Sousa, Gabrielle Maciel de; Caurio, Emanuele Pozzebon; Guanilo, Maria Elena Echevarría; Girondi, Juliana Balbinot Reis (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: Identify nursing interventions that contribute to the reduction of surgical site infections in potentially contaminated surgeries. Methods: Integrative review, carried out in four databases. There were 5,888 articles published in the period from January 2008 to July 2018, in English, Portuguese and Spanish, from which nine articles were selected after final analysis. Results: The nursing interventions appeared according to the perioperative periods: preoperative (55.55%), intraoperative (33.33%), postoperative (66.66%), being associated with: antibiotic therapy, trichotomy, alcoholic chlorhexidine bathing, hand hygiene, sterile glove/wear/ package change for fascia and skin closure, degermination, antisepsis, surgical classification, surgical time, care with dressings and drains, temperature and blood glucose control, patient education, discharge and post-hospital discharge orientation. Conclusions: Nursing interventions were identified in each perioperative period, proving to be essential for the qualification of nursing care and effective in reducing surgical site infection in potentially contaminated surgeries.